The Scars of Civil War : The Long-Term Welfare Effects of the Salvadoran Armed Conflict - Acosta, Pablo; Baez, Javier E.; Caruso, German; Carcach, Carlo (World Bank, Washington, DC, 2020)
This paper estimates the long-term effects on human capital accumulation and subsequent labor market outcomes of in utero and early childhood exposure to the civil war in El Salvador (1980-92), the second longest and deadliest civil conflict in Central America. Identification is obtained from spatial and intertemporal variation in the intensity of the conflict drawn from historical archive data comprising records of human casualties, disappearances, and refugees. The results show that people born in highly violent areas during the civil war saw a reduction in their probability of being employed by 6 percentage points, and of getting a high-skilled job by 5 percentage points, 20 to 30 years after it happened. The civil war also reduced their education by 0.8 year, as well as their enrollment and literacy rates. Subgroup analysis indicates that exposed males and indigenous groups experienced the largest losses in human capital and had weaker performance in the labor market.